NUTRITION: A PARADIGM SHIFT IN AGING CONCEPT? : Life Science-Molecular Biology - KUMARI, DEVA; RADHAKRISHNAN, YASHWANTH (International Journal of Life Science and Pharma Research, 2012)
'Ageing' is an outcome of diverse metabolic phenomena like entropy, mitochondrial aging, physiological stress, environmental stress and genetic stress. Antioxidants have long been thought to be involved in delaying ageing processes and a lot of attention has been paid to identifying suitable antioxidants. Cellular studies have also demonstrated that generation of reactive oxygen species in mitochondria due to various stress, results in damage of macro molecules, thus leading to rapid and enhanced cellular ageing. However, recent evidences, at least in higher organisms, suggest that the ageing processes are much beyond single molecule such as anti oxidants. Longevity can also stems from maternal nutrition and fetal nutrition. Further during its life time, the quantity (calorie restriction) and quality of nutrition along with life style impact aging. In addition, the body composition and the ability to regulate energy have been suggested to have a role in metabolic dysregulation leading to diabetes, obesity and cardio vascular disorders, which in turn accelerate aging process. Nutrients either available in the basic food matrix or as single molecules, have been shown to act via several mechanisms, to help the cells to cope with the effects of cellular oxidative stress and prevent rapid aging. Novel concepts such as exercise mimetics seem to hold promise to health and aging since they are being looked up to as a potential target in pharmaceuticals and functional food industry. This review summarizes the contributions of nutrition in understanding the molecular concepts of aging.